2017
DOI: 10.1186/s12889-017-4611-2
|View full text |Cite|
|
Sign up to set email alerts
|

Acceptability of lifelong treatment among HIV-positive pregnant and breastfeeding women (Option B+) in selected health facilities in Zimbabwe: a qualitative study

Abstract: BackgroundZimbabwe’s Ministry of Health and Child Care (MOHCC) adopted 2013 World Health Organization (WHO) prevention of mother-to-child HIV transmission (PMTCT) guidelines recommending initiation of HIV-positive pregnant and breastfeeding women (PPBW) on lifelong antiretroviral treatment (ART) irrespective of clinical stage (Option B+). Option B+ was officially launched in Zimbabwe in November 2013; however the acceptability of life-long ART and its potential uptake among women was not known.MethodsA qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 21 publications
(19 reference statements)
7
56
1
Order By: Relevance
“…This support can be like remind to take their drugs and counseling. The findings described in this study were similar to those reported in other studies in Zimbabwe [21] partner, community and health worker support were facilitators to PMTCT service utilization. Other study also had similar findings [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This support can be like remind to take their drugs and counseling. The findings described in this study were similar to those reported in other studies in Zimbabwe [21] partner, community and health worker support were facilitators to PMTCT service utilization. Other study also had similar findings [31].…”
Section: Discussionsupporting
confidence: 90%
“…Frequently mentioned individual and family related factors identified in this study were fear of divorce, lack of family support, lack of partner support and lack of time. Like our research, other studies found that non-disclosure of HIV status, fear of divorce, fear of HIV stigma, and lack of partners support were some of the most common barriers to PMTCT service utilization [16,[19][20][21][22][23][24][25][26]. Another study in Sudan [27], and in Malawi [28] also revealed that women are not likely to disclose their HIV status due to stigma.…”
Section: Discussionsupporting
confidence: 72%
“…We observed that the initiation of ART on the same day as HIV diagnosis significantly increased both the risk of having an NFU status and non-retention, confirming that pregnant women may still experience considerable staff pressure to undergo immediate ART initiation without sufficient time to disclose to their partner or relative or reflect on their HIV serostatus and the implications of lifelong treatment [16][17][18]21]. A greater degree of acceptability of lifelong treatment under Option B+ can be achieved with male-partner knowledge and support as well as strengthened community sensitization [22,23]. The strengths of our study lie in the number of sites included, which resulted in the inclusion of more than 40 000 eligible women in the analysis, increasing the statistical power and reliability of our results.…”
Section: Discussionmentioning
confidence: 86%
“…More than 12% of the women had no education, 63% were unemployed and 56% were in a couple or married. The median gestational age at ART initiation for the 'B+ pregnant' women was 25 weeks (IQR: [19][20][21][22][23][24][25][26][27][28][29]. The median follow-up time under ART was 13 months (IQR: .…”
Section: Attrition Risk At 12 Months After Art Initiationmentioning
confidence: 99%
“…However, only a handful of studies on ART barriers have been conducted after the implementation of universal Test and Treat [12,13]. Literature from Option B +, a policy that has provided universal treatment for pregnant/breastfeeding women since 2016, found unique barriers to ART initiation among healthy women, including concerns about partner support, feeling healthy, poor knowledge about early ART initiation, needing time to accept their new status, and fear of side effects [15][16][17][18]. Additional information is needed to understand how ART initiation barriers may be similar or different for healthy clients under new universal Test and Treat policies compared to barriers described under prior guidelines that used clinical staging to determine ART eligibility.…”
Section: Introductionmentioning
confidence: 99%